Ruthenium-BINAP Catalyzed Alcohol C-H tert-Prenylation via 1,3-Enyne Transfer Hydrogenation: Beyond Stoichiometric Carbanions in Enantioselective Carbonyl Propargylation - Nguyen, Khoa D. (J Am Chem Soc, 2016)
The chiral ruthenium complex formed in situ from (TFA)(2)Ru(CO)(PPh(3))(2) and (R)-BINAP is found to catalyze the enantioselective C-C coupling of diverse primary alcohols with the 1,3-enyne, TMSC≡CC(Me)=CH(2), to form secondary homopropargyl alcohols bearing gem-dimethyl groups. All reagents for this byproduct-free coupling are inexpensive and commercially available, making this protocol a practical alternative to stoichiometric carbanions in enantioselective carbonyl reverse prenylation.